Blue tights - Williams-Garcia, Rita. (New York : Puffin Books, 1996)
Growing up in a city neighborhood, fifteen-year-old Joyce, unsure of herself and not quite comfortable with her maturing body, tries to find a place to belong and a way to express herself through dance.
Booklist.
Books for the Teen Age (NYPL).
School Library Journal.
7.3.
Young Adult
Keywords: African Americans -- Fiction; City and town life -- Fiction; Dance -- Fiction; Self-confidence -- Fiction; African Americans -- Fiction; City and town life -- Fiction; Dance -- Fiction; Self-confidence -- Fiction